Editorial - The Australian Journal of Indigenous Education (The Australian Journal of Indigenous Education, 2013)
We are very pleased to bring you Volume 42.1 of the Australian Journal of Indigenous Education. The articles in this Volume collectively address the urgent need to disrupt ‘business as usual’ in Indigenous education in national and global contexts, and in doing so, engage in new ways of thinking and framing policy and pedagogy. Currently in Australia, discussions around what ‘counts’ as ‘good’ policy and pedagogy in Indigenous education are increasingly placed in conversation with one of three agendas: Noel Pearson's ‘radical vision’ for contemporary schooling for Indigenous students, with a renewed emphasis and return to direct instruction; Chris Sarra's ‘stronger and smarter’ strategy, which promotes a commitment to a high-expectation, high-performance and a relational approach to Indigenous education; and initiatives driven by the ‘Closing the Gap’ reform agenda. Indeed, situated within the present climate of neo-liberalism orchestrating policy by numbers, there is ‘serious stuff’ happening at the moment that impacts in very real ways on the experiences and outcomes of our Indigenous children at all levels of schooling, the capacity of teachers to work within an Indigenous Australian education space for both Indigenous and non-Indigenous students, and the positioning of education as a location of possibility for ‘doing business differently’. The time for us as educators and researchers has never been more urgent — we have to be the ones to talk loud and to talk strong against colonial and neo-colonial moves to silence and exclude the counter stories we have to tell. In conversation as Indigenous and non-Indigenous educators working towards social justice in education, the articles in this Volume bring us these narratives.